Analisis Faktor Yang Berhubungan Dengan Kesiapsiagaan Terhadap Bahaya Kebakaran di Rumah Sakit - Anggi Nadzifa Nauli Vasha; Abdurrozaq Hasibuan (PT. Alahyan Publisher Sukabumi, 2024)
Preparedness is a series of activities carried out by the organization to anticipate disasters and carried out with the right steps. Hospitals are one of the places that have a risk of fire. The use of electrical equipment, short circuits, and gas and chemical cylinders are some of the things that cause fires in hospitals. This study has the aim of knowing how the factors associated with preparedness for fire hazards in hospitals. The method used was literature review by analysing 10 articles or journals from various sources. The results showed from the articles reviewed that the Factors Associated with Preparedness for Fire Hazards in Hospitals, namely there are two factors that are related, namely predisposing factors and reinforcing factors.